Economic Performance and Economic Growth in the Early Islamic World - Shatzmiller, Maya (Journal of the economic and social history of the Orient, 2011)
Abstract The author argues that in the case of Islamic history, the growing interest in the economic theory of institutions and their role in economic growth has shifted the scholarly methodology from empirically based research, to theoretical models which favoured sweeping generalizations about the negative roles of the Islamic state and legal institution. Shatzmiller’s examinations of the role of Islamic institutions in periods of economic growth show that economic growth was visible in the key indicators of the Caliphate’s economy between ca. 750 and ca. 1100. The conclusion is that there was nothing intrinsic to Islamic institutions that impaired economic growth.